VIRTUAL PROJECT FOR VIRTUAL ECONOMY: ABOUT CRYPTO CURRENCY AND OTHER ISSUES - V. I. Karpunin (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The reasons not of trivial professional interest in a phenomenon of Crypto currency (cryptocurrency) in general and Bitcoin (Bitcoin) in particular have induced to undertake judgment, and then and public statement in the scientific magazine of the subject announced in the name of article. This interest has been dictated at all not by an opportunity to clear narrow, special questions: essences, the nature, features of functioning and regulation of the market of cryptocurrencies in the professional academic environment. The nature of the actual public illumination of a number of aspects of the cryptocurrency industry, including possibility of ICO, at the V International scientific and practical conference "Administrative Sciences in the Modern World" which was taking place in Financial University under the Government of the Russian Federation (December, 2017), in particular, the report of the associate professor of the Financial university M. E. Kulagina "Separate aspects of attraction of investments into the business by means of ICO" carrying can be an example of manifestation of trivial professional interest in this subject if to speak about the scientific party of a conference, information character, naive and no more than informative for profane persons. Or, for example, a public (open) lecture for students on legal regulation a blockchain technologies of professor of department of criminal law, criminal trial and criminalistics of MGIMO (U) E. L. Sidorenko. At a lecture besides students there was also a Deputy Prime Minister of Russia I. I. Shuvalov. Our interest has been dictated by other circumstances. This interest the phenomenology of the power, the theory which concept is proved and submitted by us to scientific community in a number of publications including in article "Phenomenology of the power affects unconditional need of further judgment and development of the theory: genesis of forms of manifestation of a global system contradiction "creditors are debtors".